Luteolin alleviates methionine–choline-deficient diet-induced non-alcoholic steatohepatitis by modulating host serum metabolome and gut microbiome - Guo, Wei; Luo, Lianxiang; Meng, Yan; Chen, Wen; Yu, Lixiu; Zhang, Cong; Qiu, Zhenpeng; Cao, Peng (Frontiers in Nutrition, 2022)
Background and purpose: Previous studies have indicated the protective effects of luteolin against non-alcoholic steatohepatitis (NASH), but the definite underlying mechanism still remains unclear. The current study aimed to explore the metabolomic and metagenomic signatures of NASH with luteolin supplementation. Experimental approach: Mice were fed with a methionine-choline deficient (MCD) diet containing 0.05% luteolin for 6 weeks. NASH severity was determined based on liver histological observations, serum and hepatic biochemical measurements. Targeted metabolomics was conducted to identify differential metabolites in mice serum. 16S rRNA sequencing was conducted to assess the gut microbiota composition and function in mice colon. Results: In detail, luteolin treatment significantly alleviated MCD diet-induced hepatic lipid deposition, liver function damage, and oxidative stress. Targeted plasma metabolomics revealed that 5-hydroxyindole, LPE (0:0/22:5), indole 3-phosphate, and N-phenylacetylphenylalanine were remarkably elevated, and homogentisic acid, thiamine, KN-93, PC (16:1e/8, 9-EpETE), carnitine C9:1-OH, FFA (18:4) and carnitine C8:1 were significantly decreased in NASH group as compared with normal group, which could be profoundly reversed after luteolin treatment. 16S rRNA sequencing indicated that luteolin supplementation significantly increased Erysipelatoclostridium and Pseudomonas as well as decreased Faecalibaculum at genus level. Most importantly, a negative association between thiamine and Faecalibaculum was observed based on Spearman correlation analysis, which may play an important role in the preventive effects of luteolin against NASH. Conclusion: Collectively, luteolin may alleviate the NASH by modulating serum metabolome and gut microbiome, which supports its use as a dietary supplement for NASH prevention.